2019
DOI: 10.1038/s41437-018-0177-8
|View full text |Cite
|
Sign up to set email alerts
|

MHC class I diversity predicts non-random mating in Chinese alligators (Alligator sinensis)

Abstract: The major histocompatibility complex (MHC) has several important roles in kin recognition, pathogen resistance and mate selection. Research in fish, birds and mammals has suggested that individuals optimise MHC diversity, and therefore offspring fitness, when choosing mates. In reptiles, however, it is unclear whether female mate choice is based on genome-wide genetic characteristics such as microsatellite DNA loci, particular functional-trait loci (e.g., MHC) or both, and MHC's effects on mate choice remain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Second, some studies have reported that individuals with higher diversity or heterozygosity at the MHC were favoured as partners (Cutrera et al, 2012; Landry et al, 2001; Richardson et al, 2005; Winternitz et al, 2015). Third, in terms of MHC compatibility, MHC‐dependent disassortative mating has been reported, which could maximise the MHC diversity of offspring (Han et al, 2019; Hoover et al, 2018; Schwensow et al, 2008; Setchell et al, 2010). Several studies have also demonstrated that MHC genes could be a cue for kin recognition enabling avoidance of mating with relatives through MHC‐associated odours (Grob et al, 1998; Milinski, 2006; Penn, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, some studies have reported that individuals with higher diversity or heterozygosity at the MHC were favoured as partners (Cutrera et al, 2012; Landry et al, 2001; Richardson et al, 2005; Winternitz et al, 2015). Third, in terms of MHC compatibility, MHC‐dependent disassortative mating has been reported, which could maximise the MHC diversity of offspring (Han et al, 2019; Hoover et al, 2018; Schwensow et al, 2008; Setchell et al, 2010). Several studies have also demonstrated that MHC genes could be a cue for kin recognition enabling avoidance of mating with relatives through MHC‐associated odours (Grob et al, 1998; Milinski, 2006; Penn, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Second, some studies have reported that individuals with higher diversity or heterozygosity at the MHC were favoured as partners (Cutrera et al, 2012;Landry et al, 2001;Richardson et al, 2005;Winternitz et al, 2015). Third, in terms of MHC compatibility, MHC-dependent disassortative mating has been reported, which could maximise the MHC diversity of offspring (Han et al, 2019;Hoover et al, 2018;Schwensow et al, 2008;Setchell et al, 2010).…”
mentioning
confidence: 99%
“…We took a population survey for MHC-I and MHC-IIB genes in previous studies (Zhai et al, 2017;Han et al, 2019). Unlike the various high alleles found in MHC-IIB in Chinese alligator, only I1327 (Alsi-I7), I20 (Alsi-Iψ-BAC32), and Beta1085 (Alsi-IIB11) were found all dimorphic: two alleles at each locus (Zhai et al, 2017).…”
Section: Evolutionary Hypothesis Of Major Histocompatibility Complex ...mentioning
confidence: 99%
“…In our previous study, the BAC library was constructed (He et al, 2012), the genome was sequenced (Wan et al, 2013), and the differential mRNA expression of several tissues of the Chinese alligator was investigated (Lin et al, 2018) to understand the immune system and genetic basis of sex determination and longdiving behavior. Furthermore, MHC genes were investigated to study MHC-associated mate choice in Chinese alligators (Han et al, 2019). Together, all these studies make it possible to tackle the unanswered questions about the MHC architecture in Crocodylia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have reported that individuals with higher diversity or heterozygosity at the MHC were favoured as partners (Landry, Garant et al 2001, Richardson, Komdeur et al 2005, Cutrera, Fanjul et al 2012, Winternitz, Promerova et al 2015). In terms of MHC compatibility, MHC-dependent disassortative mating has been reported, which could maximise the MHC diversity of offspring (Schwensow, Eberle et al 2008, Setchell, Charpentier et al 2010, Hoover, Alcaide et al 2018, Han, Sun et al 2019). However, as excessive expression of MHC molecules could lead to depletion of the mature T-cell repertoire and elevated risk of autoimmune disease, it has also been suggested that individuals may optimise rather than maximise MHC diversity (Reusch, Haberli et al 2001, Griggio, Biard et al 2011, Rekdal, Anmarkrud et al 2019).…”
Section: Introductionmentioning
confidence: 99%